Game theory techniques for balancing active power in a low-voltage microgrid - Affelt, J.; Lisowski, J. (Scientific Journal of Gdynia Maritime University, 2017)
The article discusses the problem of developing a concept of fully distributed Demand Side Management in a low-voltage microgrid, using an algorithm based on game theory. The following solution can be used as a primary method to maintain the balance of active power and as a backup system in a case of switching the microgrid to isolated mode, and also in Smart Power Grid in a situation where there is a loss of communication between the controllers.